Characterisation of suspended and sedimented particulate matter in blue-green infrastructure ponds. Issue 1 (30th May 2020) - Krivtsov, V.; Arthur, S.; Buckman, J.; Kraiphet, A.; Needham, T.; Gu, Wanying; Gogoi, Prasujya; Thorne, C.
Abstract: Blue-green infrastructure (BGI) ponds have an important function of alleviating flood risk and provide water quality improvements among other multiple benefits. Characterisation of bottom sediments and suspended particulate matter (SPM) is understudied, but is indispensable for assessing the ponds' functioning because of their role in biogeochemical cycling and pollutant adsorption. Here we report on the analysis of particle sizes and chemistry from multiple locations. The results have shown that SPM in these ponds includes particles of both biological and abiotic origin, and the in situ produced organic matter constitutes a major part of SPM. The relevance of biological processes is often overlooked, but a combination of scanning electron microscopy (SEM) observations and chemical analysis highlights its primary importance for characterisation of the particulate matter. A considerable proportion of both suspended and sedimented particulates is smaller than 100 microns. There is normally a large fraction of small silt-sized particles, and often a considerable proportion of very fine particles (clay-size). Although for some spectra unimodal distribution has been observed, in many cases the revealed particle size distribution (PSD) was bimodal, and in some instances more than two modes were revealed. A complex PSD would be expected to result from a combination of simple unimodal distributions. Hence the multimodality observed may have reflected contributions from different sources, both abiotic and biological. Furthermore, many smaller particles appear to be interconnected by detrital matter. Among chemical elements routinely detected within the SPM in significant concentrations were Si, Al, Ca, Mg, Fe, K, Mn, P, Cl and S. In a number of cases, however, there were less expected elements such as Ti, Y, Mo, Cr and even Au; these may have reflected the effect of car park and road runoff and/or industrial pollution. Most of these elements (except Mo and Au) and up to 30 others were also routinely detected in sediment samples. Such pollutants as Co, Cu, Ni, Zn and As were detected in bottom sediments of all ponds. There were a number of correlations between pollutants in sediments and the particle's median diameter. However, aggregation leads to large low density flocks and masks correlation of chemicals with SPM particle size. Statistical associations among the elements aided the understanding of their sources and pathways, as well as the underlying biological and abiotic processes. Specifically, our analysis implicated contributions from such sources as allochthonous and autochthonous detritus, roadside and industrial pollution, biologically induced precipitation, and discarded electronics. Elevated levels of rare earth elements (REE) and other trace elements open a possibility of their recovery from the sediments, which should be considered among the multiple benefits of BGI. Graphical Abstract